Students’ Views on the Use of Educaplay in Indonesian Learning at Elementary School - Nur Asih, Dian; Werdiningsih, Dyah (International Journal of Language Teaching and Education, 2026)
This study aims to describe the perception of elementary school students towards the use of Educaplay educational games in Indonesian learning. The research uses a qualitative method with a descriptive design. Data were collected through semi-structured interviews with students who had used Educaplay and questionnaires to corroborate the results of the interviews. The participants in this study amounted to 3 students. Interview data was transcribed and analyzed, then combined with the results of the questionnaire. The results show that Educaplay is considered to have an attractive appearance, easy-to-use features, and increase learning motivation that is felt directly by students. Regarding the implementation of the use of Educaplay quizzes, students are divided into two opinions, students choose to be carried out at the beginning of learning as a way to recover energy after previous learning activities and students choose at the end of learning as a conclusion and evaluation of fun learning.